Cinema e formação: os imaginários de jovens professoras sobre o audiovisual “K-12” - Dutra, Larissa Rosso (2024)
This dissertation explores the intersection of cinema, education, and teacher training, using Melanie Martinez's film "K-12" (2019) as a central pedagogical device. The research investigates how audiovisual media can act as a catalyst for critical reflection and social transformation within the educational context. The study is grounded in the hermeneutics of Hans-Georg Gadamer (1997) and the social imaginary theories of Cornelius Castoriadis (1982, 1987, 1999, 2004), providing a solid foundation to question and reimagine the role of education and initial teacher training. The primary aim was to understand how pre-service teachers attribute meanings to the "K-12" device. The methodology employed was the narrative approach proposed by Josso (1988, 2004, 2007), with an emphasis on Gadamer's (1997) comprehensive hermeneutics. The research combined qualitative and quantitative methods to comprehensively analyze the participants' responses to the film, investigating how their personal experiences and interpretations contributed to a deeper understanding of the film's themes and their implications for pedagogical practice. The results revealed that "K-12" has a significant impact on teacher training, promoting critical reflection on educational structure. The film, as a device, acts as a mirror to school experiences, challenging established norms and encouraging a more reflective and inclusive pedagogical approach. The integration of the film's interpretations into teaching practices showed potential for transforming education by fostering greater critical awareness and innovative teaching methods. Thus, it concludes that using audiovisual devices like "K-12" can enrich teacher training by provoking reflections and promoting social transformation within the school environment. The study highlights the importance of incorporating hermeneutic perspectives, imaginaries, and creative pedagogical practices in education, suggesting that audiovisual media can play a crucial role in the evolution of educational practice and the building of a more conscious and reflective society.